English reading achievement among ESL lower secondary students: which girls and Wwich boys? - Badrasawi, Kamal J I; Abu Kassim, Noor Lide (2017)
Literature has shown that boys are underachieving in educational performance; they are becoming more and more disengaged with learning; and their retention rates in schools have dropped considerably. Though the problem of underachievement and disengagement with learning is largely associated with boys, not all boys are underachieving or disengaged with learning, and not all girls are achieving and engaged with learning. There is evidence to suggest that differences within groups of boys and girls are more significant than differences between gender i.e. it is likely that students’ educational performance is highly influenced by socio-demographic factors such as school location, race, parents’ socio-economic status, and parents’ education. Hence, this study aims to compare and identify groups of students who are at risk of underachieving in English reading skill. A sample of 944 Malaysian ESL Form 1, 2 and 3 students randomly selected from national-type schools participated in the study. A test of English reading skill, including 60 items, was used. The Rasch Measurement Model analysis in addition to descriptive and inferential analyses were used to answer the research questions. The results showed that students’ performance in English reading differed from one group to another, implying that gender did not exclusively influence student performance. Based on the findings, more sound and informed decisions on students’ performance in English reading skill and the most effective teaching methods could be made. Qualitative investigation of the factors behind high or low performance among the schools is needed. Key words: English reading skill; Rasch Model; demographic factors; underachievement